Feed intake and nutrient utilization in Sirohi, Marwari and Kutchi breeds of goat under intensive system of feeding management (Indian Journal of Animal Production and Management, 2024)
Comparative feed intake and nutrient utilization were studied in adult bucks of Sirohi, Marwari and Kutchi  breeds. The bucks were provided Cajanus cajan straw ad libitum as basal roughage, concentrate mixture  400 g/buck/day and green grass (Cenchrus ciliaris) one kg /buck/day as a supplement. The intake of DM,  OM and CP were significantly less in Marwari bucks, whereas these values were similar between Sirohi  and Kutchi. Total water intake /kg DM intake was similar in all the three breeds. Significantly (p
Keywords: Goat breeds; India; Intensive system of feeding management; Nutrient intake; Nutrients’ digestibility